Effectiveness and safety of dupilumab in the treatment of pediatric atopic dermatitis: a real-world study from China - Xu, Yue; Li, Bowen; Wang, Wenge (Frontiers in Immunology, 2025)
BackgroundAtopic dermatitis (AD), a common chronic inflammatory skin disorder in children, often shows limited response to conventional therapies with potential adverse effects.MethodsThis real-world study evaluated dupilumab—a monoclonal antibody targeting IL-4/IL-13 signaling—in 59 Chinese pediatric patients (aged 6 months–12 years) with moderate-to-severe AD, stratified by body weight. Over a median 33-week follow-up (up to 96 weeks), we dynamically assessed efficacy metrics including Eczema Area and Severity Index (EASI), Peak Pruritus Numerical Rating Scale, and Dermatology Life Quality Index, alongside systematic surveillance of treatment-emergent adverse events (TEAEs).ResultsAt Week 16, 68.97% (40/58) achieved EASI-75, accompanied by significant symptom relief (68.17% itch reduction; 77.4% quality-of-life improvement). Efficacy persisted beyond Week 16 (>58.82% sustained EASI-75) without age or sex differences. TEAEs occurred in 25.42% (15/59) of patients, primarily conjunctivitis (10.17%) and paradoxical eczema flares (5.08%). Notably, we report the first pediatric cases of acute rash exacerbation within 72 hours post-initial dose (3 patients, EASI increase: 39.90%–61.13%) and a unique late-onset pustular dermatitis with fever.ConclusionThese findings confirm dupilumab’s sustained effectiveness and manageable safety in Chinese children with AD while highlighting the need for vigilance against early paradoxical flares and rare inflammatory reactions, providing critical real-world evidence for long-term use in this population.